DESEMPENHO AGRONÔMICO DE LINHAGENS AVANÇADAS DE AMENDOIM NA REGIÃO CONE-SUL DE MATO GROSSO DO SUL - GAIOLA, Lucas Henrique de Oliveira; SCHWARTZ, Phillip Silva; GOTTARDI, Gabriel Alves; OLIVEIRA, João Paulo Zaluchi Souza de; PESTANA, Carlos Eduardo Skittberg; ZOZ, Tiago (ANAIS DO ENIC, 2025)
-